Cardiorenal Syndrome in Patients with Chronic Kidney Disease and Diabetes Mellitus (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Combined damage to the cardiovascular system and kidneys is currently being considered within the framework of cardiorenal syndrome (CRS).In this study, the prevalence and risk factors associated with the development of left ventricular hypertrophy (LVH) in patients at the predialysis stage of chronic kidney disease (CKD) of various etiologies were studied.